Preparation and Characterization of Chitosan/Poly(Vinyl Alcohol) Blended Films: Mechanical, Thermal and Surface Investigations - Esam A. El-Hefian; Mohamed Mahmoud Nasef; Abdul Hamid Yahaya (E-Journal of Chemistry)
In this study, blends of chitosan (CS) and polyvinyl alcohol (PVA) (CS/PVA) having various proportions were prepared and characterized by universal mechanical tester, the differential scanning calorimetry (DSC) and contact angle measurements. Studying the mechanical properties of the films showed that blending improved the tensile strength, which increased with increasing PVA content up to 40% while the elongation% at break of the blends was decreased compared to that of the pure components. The obtained results of DSC suggested that some interaction between chitosan and PVA mostly took place. Static water contact angle measurements showed an improvement in the wettability of the obtained films.